PRL-3 disrupts epithelial architecture by altering the post-mitotic midbody position - Luján Miralles, Pablo; Varsano, Giulia; Rubio, Teresa; Hennrich, Marco; Sachsenheimer, Timo; Gálvez-Santisteban, Manuel; Martín-Belmonte, Fernando; Gavin, Anne-Claude; Brügger, Britta; Köhn, Maja (Journal of cell science, 2016)
Skip to Next Section - Disruption of epithelial architecture is a fundamental event during epithelial tumorigenesis. We show that the expression of the cancer-promoting phosphatase PRL-3 (PTP4A3), which is overexpressed in several epithelial cancers, in polarized epithelial MDCK and Caco2 cells leads to invasion and the formation of multiple ectopic, fully polarized lumens in cysts. Both processes disrupt epithelial architecture and are hallmarks of cancer. The pathological relevance of these findings is supported by the knockdown of endogenous PRL-3 in MCF-7 breast cancer cells grown in three-dimensional branched structures, showing the rescue from multiple-lumen- to single-lumen-containing branch ends. Mechanistically, it has been previously shown that ectopic lumens can arise from midbodies that have been mislocalized through the loss of mitotic spindle orientation or through the loss of asymmetric abscission. Here, we show that PRL-3 triggers ectopic lumen formation through midbody mispositioning without altering the spindle orientation or asymmetric abscission, instead, PRL-3 accelerates cytokinesis, suggesting that this process is an alternative new mechanism for ectopic lumen formation in MDCK cysts. The disruption of epithelial architecture by PRL-3 revealed here is a newly recognized mechanism for PRL-3-promoted cancer progression.